A prototype object-oriented finite element method program: Class hierarchy and graphic user interface - Gajewski, R. Robert; Kowalczyk, Tomasz (Computer Assisted Methods in Engineering and Science, 2023)
The paper considers the application of an object-oriented approach to the development of FEM software. A brief introduction to basic concepts of object-oriented modelling is given, followed by a short overview of developed classes. Objects, classes, methods and inheritance are illustrated using a graphical representation. The design, implementation and maintenance of an object-oriented program is compared to that of an equivalent procedural program in order to identify advantages of the object-oriented approach. Some design problems of conventional finite element analysis software and their possible solutions offered by the object-oriented methodology are identified and discussed.